Protein-protein interaction of LDH and CRP-1 with hematotoxin snake venom proteins of all species of snake: An in silico approach - Honutagi, Rajesh M.; Sunil , R.; Patil, S.M.; Bhosale, Supriya; Das, Swastika N.; Parvatikar, Prachi P.; Das, Kusal K. (International Journal of Health Sciences, 2023)
Objective: Snake bite-induced elevation of serum LDH and CRP-1 is considered as useful biomarkers of hemotoxic. The snake venom contains proteins and may result in various envenomation such as bleeding, inflammation, and pain, cytotoxic, cardiotoxic, or neurotoxic effects. This in silico study was aimed to screen the snake venom proteins and to find out the most interactive hemotoxic venom protein against LDH and CRP-1 proteins as biomarkers. Methods: To validate the hypothesis of the prospective interaction of snake venom proteins, molecular docking analysis was used in the current work by deploying a cutting-edge docking program. Snake venom peptides were screened from literature and both peptide as well as target protein were obtained from PDB. HDOCK online server was used for the molecular docking analysis of target proteins with hemotoxic snake venom peptides. Further, the toxicity properties of each docked complex of target proteins were subjected for ADME/T analysis. Results: The selected snake venom peptides were subjected to molecular docking study and the results generated from computational-based approach reveals that all the hematotoxin snake venom proteins are interactive with LDH and CRP-1 peptide. Further, this study indicates that snake venom metalloproteinase (SVMPS) peptide may be considered as the best interactive protein with both LDH and CRP-1 proteins; also, ADME/T screening revealed that all docked complex are safe and follow toxicity properties. Conclusion: This in silico study clearly shows that the greatest interaction of SVMPS peptide with LDH and CRP-1 may be due to strong binding in the active site of the target proteins LDH and CRP-1 with SVMPS. Results, further, confirmed LDH and CRP-1 as potential biomarkers against hemotoxic snake venoms. This study should be validated by in vitro and in vivo analysis as well as specific species snake venom should be assessed. For further studies, SVMPS can be consider as therapeutic point of view.